Studies on the predator Apertochrysa astur (Banks) (debris carrying green lacewing) on invasive coconut whiteflies - Remoniya, X.; Nelson, S. Jeyarajan (Journal of Plantation Crops, 2022)
The invasive whitefly species, rugose spiralling whitefly (RSW) and Bondar’s nesting whitefly (BNW) (Hemiptera: Aleyrodidae) were reported on coconut in 2016 at Pollachi, Tamil Nadu, India and in 2019 in Kerala, India, respectively. Among the natural enemies of whiteflies, Apertochrysa astur (Banks) is the predominant predator observed in the coconut ecosystem. The population effect of RSW and BNW in different host plants, viz., coconut, banana and custard apple, on the growth and development of the A. astur were studied. Further, the effects of A. astur and yellow sticky traps (YSTs) were evaluated against the invasive whiteflies of coconut. The growth and development of the grubs of A. astur were better when fed with the RSW and BNW reared in coconut, followed by custard apple and banana. The weight of the 1st, 2nd and 3rd instar grubs were 0.25 mg, 0.62 mg and 2.46 mg, respectively. The pre-pupal weight was 7.41 mg, and that of the pupa and adult were 8.35 mg and 12.27 mg when fed with RSW. Similarly, when A. astur was fed with BNW reared on coconut, the weight of the 1st, 2nd and 3rd instar grub of A. astur was 0.22 mg, 0.59 mg and 2.24 mg, respectively. The pre-pupal weight was 7.06 mg, and that of the pupa and adult were 8.22 mg and 12.01 mg, respectively. Among the different treatment dosages of A. astur eggs and YSTs evaluated, 3 YST and 10 A. astur eggs palm-1 were highly effective as they reduced RSW and BNW population by 59.7 per cent and 56.7 per cent per cent, respectively. The grubs of A. astur were observed to be extremely efficient in reducing the population of A. rugioperculatus and P. bondari. The results supported that A. astur can be employed as an efficient biological control agent for managing invasive whitefly species in the coconut ecosystem.